Exploration on the Reform of Training Mode of Biochemistry Engineering Talents under the New Engineering Background：Taking the Blended Teaching Mode of "Biochemistry" as an Example - Qin WANG; Yunxiang HE; Yao JIN; Junling GUO (Pige Kexue Yu Gongcheng)
Blended teaching is an inevitable trend in the field of higher education in response to the global digital challenge. The introduction of blended teaching reform in talent cultivation and the exploration of a new ideological and political blended teaching mode can fully explore the convenience of online courses in the forefront of the subject and the high efficiency of offline courses in imparting knowledge, so as to improve the effectiveness of education. Biochemistry is the core course in the training of biochemistry engineering talents. Aiming at the problems of "Biochemistry" course in three dimensions of knowledge transference, ability cultivation, and value guidance, based on Outcomes-Based Education concept and Problem-Based Learning model, this article constructed the case base for teaching and ideological and political, and adopted Online to Offline teaching model and whole process evaluation. This carried on systematic teaching innovation to the course, and achieved initial results, which provided a new idea for the training and teaching reform of biochemistry engineering talents under the new engineering background.